Candida albicans adherence on acrylic resin plates immersed in black tea steeping - Soebagio Soebagio (Faculty of Dental Medicine, Universitas Airlangga https://fkg.unair.ac.id/en, 2010)
Background: Black tea or Cournelia sinensis is one of known tea varieties in Indonesia. Actually, black tea is consumed daily as beverage that can function as antiseptics and fungicides. Black tea containing antibacterial and fungicide properties can reduce the number of Candida albicans (C. albicans) colony attachment on the surface of acrylic resin plates. Purpose: This study was done to determine the effective concentration of black tea steeping used as the immersion material of acrylic resin plates towards the number of Candida albicans colonies. Methods: In this study, acrylic resin plates with the size of 10 × 20 × 1 mm were immersed in black tea steeping with the following concentrations, 3.33%, 6.66%, and 13.33%, for one hour. The growth of C. albicans colonies were then detected by counting the number of colonies growing on Sabouraud’s dextrose medium. Data was analyzed by using both One-Way ANOVA with the significance level of 5%, and Tuckey’s multiple comparison tests (Tuckey’s HSD test). Results: There were significant differences in the number of C. albicans colonies in acrylic resin plates immersed in black tea with the concentration of 3.33%, 6.66%, and 13.33%. Conclusion: It can be concluded that the higher concentration of black tea (13.33%) used to immerse acrylic resin plates, the greater the decreased number of C. albicans colonies.Latar belakang: Teh hitam atau Cournelia sinensis adalah salah satu macam teh yang dikenal di Indonesia. Teh hitam seringkali dipakai sebagai minuman sehari- hari dan berkhasiat sebagai antiseptik maupun fungisid. Teh hitam yang mengandung sifat antibakteri dan fungisid dapat menurunkan jumlah koloni Candida albicans (C. albicans) yang melekat pada permukaan lempeng resin akrilik. Tujuan: Untuk mengetahui konsentrasi efektif seduhan teh hitam sebagai bahan perendam lempeng resin akrilik terhadap jumlah koloni C. albicans. Metode: Pada penelitian ini lempeng resin akrilik ukuran 10 × 20 × 1 mm direndam dalam seduhan teh hitam konsentrasi 3,33%, 6,66%, 13,33% selama 4 jam. Pertumbuhan jumlah koloni C. albicans dilakukan dengan cara menghitung jumlah koloni yang tumbuh pada media Sabouraud’s dextrose. Analisis data menggunakan uji anova satu arah dengan taraf kemaknaan 5%, uji pembanding ganda tuckey HSD. Hasil: Terdapat perbedaan yang bermakna jumlah koloni C. Albicans yang melekat pada lempeng resin akrilik yang direndam dalam seduhan teh hitam dengan konsentrasi 3,33%, 6,66% dan 13,33%. Kesimpulan: Konsentrasi 13,33% atau makin pekat seduhan teh hitam yang digunakan untuk merendam lempeng resin akrilik menyebabkan penurunan jumlah koloni C. albicans.